2017
DOI: 10.18203/issn.2455-4510.intjresorthop20172089
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of rearfoot angle to Q-angle in patellofemoral pain syndrome: a prospective study

Abstract: <p class="abstract"><strong>Background:</strong> Objective of the study was to evaluate the correlation between rearfoot posture to Q-angle in patients with patellofemoral pain syndrome.</p><p class="abstract"><strong>Methods:</strong> This is a two-year prospective observational study in which all patients with patellofemoral pain syndrome in the age group of 20-30 years were included in the study. The static Q-angle and the rearfoot angles of these subjects were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…Our results also showed a greater subtalar angle in the PFP group compared to the control group. Similar results were reported by the research of Dileep et al 21 , in which the patients with PFP within the ages of 20-30 years were evaluated according to their foot posture and PFP syndrome and found an association between these two components. In contrast to our study, Hetsroni et al 22 concluded that there is no consistent association between the incidence of anterior knee pain and foot pronation by measuring the subtalar joint displacement angle.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also showed a greater subtalar angle in the PFP group compared to the control group. Similar results were reported by the research of Dileep et al 21 , in which the patients with PFP within the ages of 20-30 years were evaluated according to their foot posture and PFP syndrome and found an association between these two components. In contrast to our study, Hetsroni et al 22 concluded that there is no consistent association between the incidence of anterior knee pain and foot pronation by measuring the subtalar joint displacement angle.…”
Section: Discussionsupporting
confidence: 90%
“…The CTA, which has natural relation with tibial rotational alignment was expected to be correlated with QA. This expectation may originate from the studies previously demonstrating the relationship between rearfoot position and QA in conditions like patellofemoral pain syndrome 28 . In the current study with asymptomatic participants, however, the CTA was surprisingly not represented in the final regression model either alone or in combination with other predictors.…”
Section: Discussioncontrasting
confidence: 54%
“…Another previous study reported that rearfoot misalignment causes compensatory action of the subtalar joint, which is involved in the normal function of the leg and foot during the gait cycle. Furthermore, excessive pronation of the subtalar joint inhibits foot supination and results in abnormal internal rotation of the tibia, which leads to patellar malalignment [ 28 ]. Among taekwondo athletes, sparring athletes perform kicking techniques using ground reaction force with the forefoot for the longest period of time, and forefoot pronation occurs rapidly and repeatedly, especially in situations such as maintaining distance, changing direction, and continuing skills.…”
Section: Discussionmentioning
confidence: 99%